SYSTEMATIC LITERATURE REVIEW: THE ROLE OF MSMES (MICRO, SMALL AND MEDIUM ENTERPRISES) IN IMPROVING COMMUNITY WELFARE - Basit, Abdul; Mahsun, Mahsun; Sakti, Reza Arviciena; Zahari, Yudhi Kurniawan; Prayuda, I Putu Septian Adi (Gapenas Publisher, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the economic development of Indonesia. They significantly contribute to employment, local economic growth, and poverty reduction. However, MSMEs face challenges such as limited access to capital, technological gaps, and human resource development. This research examines the role of MSMEs in improving community welfare, focusing on their contributions to income generation, job creation, innovation, and local economic diversification. Using a qualitative approach and literature review methodology, this study synthesizes secondary data from various sources, including academic journals, government regulations, and statistical data. The findings show that MSMEs contribute to community welfare by creating job opportunities, increasing local production, and driving innovation. Key indicators of welfare, such as income, housing, education, and health, are influenced by the growth of MSMEs. The study concludes that strengthening MSMEs can enhance the economic well-being of Indonesian society, highlighting the need for government support to address existing challenges and ensure sustainable development